Empowerment of Coastal Women in Developing Seaweed Processed Products in Batu Beriga Village, Central Bangka - Siti Aisyah; Aditya Pamungkas; Dini Wulansari (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Batu Beriga Village is one of the seaweed farming locations in the Province of Bangka Belitung Islands, located in Lubuk Besar Subdistrict, Central Bangka Regency. Seaweed farmers in Batu Beriga Village said that seaweed cultivation in Batu Beriga Village is still a beginner activity initiated by the surrounding community, most of whom have a background as capture fishermen. As a beginner cultivator in the seaweed sector, there are several obstacles and problems faced, including limited target consumers and marketing due to the low number of processed seaweed products in the Bangka Belitung Islands. Based on the situation analysis and partner problems, the solution offered is training for coastal women's groups to produce processed seaweed-based products that are of high quality and competitiveness. The method of activity implementation consists of counseling, exposure and discussion of partner problems regarding the importance of processed seaweed-based products and business opportunities for processed seaweed at the household scale and partner participation in program implementation. The processed seaweed product presented in the training activities was seaweed dodol. The training activity on making seaweed dodol went well. The PKK members were enthusiastic in participating in the training activities. The training activities began with a presentation on the economic value of seaweed. The next activity was to explain the types of processed seaweed that have high economic value. The dodol-making training involved several group members in assisting with the demonstration of dodol-making, starting from the preparation of tools and materials to the process of making seaweed dodol. The training was followed by a discussion session. The activity on a different day was the socialization of digital marketing, branding and marketing management with Boleh.ID partners who focus on UMKM e-commerce and were held for one day at the Batu Beriga Village PKK Multipurpose Building. The PKK members shared their interest in seaweed processing.